Linking Empowerment-Oriented Leadership to Work Engagement in Nepali Commercial Banks - Niraula, Ganesh Prasad; Kharel , Shreekrishna; Dhungana, Dipendra (Journal of Nepalese Business Studies, 2025)
This study investigates the relationship between empowerment-oriented leadership and work engagement in the banking sector. This study employed a quantitative based cross-sectional research design, data were collected from 412 banking professionals representing four private, two joint venture, and two public limited commercial banks. Respondents were chosen using stratified random sampling to ensure representation across job levels, HR departments of commercial banks. The data were collected through structured questionnaires distributed in person. Ethical approval was obtained from employees and consent was secured from all the respondents. The data and hypothesized relationships were analyzed and tested using the Statistical Package for the Social Sciences (SPSS). Construct reliability was assessed using Cronbach’s alpha, confirming the internal consistency of the measures. The results show that there is positive and significant relationship between leadership empowerment and work engagement. Similarly, there is positive and significant relationship between psychological empowerment and work engagement. However, there is insignificant and negative relationship between affective commitment and work engagement. This study contributes to the academic literature by providing empirical evidence on the influence of empowerment-oriented leadership in fostering work engagement, addressing a notable gap in prior studies that have not yet explored this relationship in the banking context. The results hold practical implications for bank managers and policymakers, suggesting that exposing empowerment-oriented leadership can serve as a strategic approach to enhance work engagement and, consequently, improve organizational performance and employee well-being.